Prinsip Moderasi Beragama I’tidal, Tawazun Dan Tasamuh Yang Terkandung Dalam Khutbah Jumat Masjid Nur Muhammad: Principles of Religious Moderation I'tidal, Tawazun and Tasamuh Contained in Friday Khutbah of Nur Muhammad Mosque - Ihwan Amalih; Ibah Turohmah; Achmad Waffiq Alfi Syahrin (Mozaic: Islamic Studies Journal, 2026)
As a nation diversity, particularly in terms of religion, we should implement the principle of religious moderation in our daily lives. To present and educate on it, we require a location that is nearby and easily accessible to the community, such as a mosque. This research was to investigate the elements of the Friday sermon and how the principles of religious moderation are practiced by the congregation. The qualitative research method was utilized, focusing on the takmir and the Friday prayer congregation as the target informants in this study. The study's conclusion indicated that the content of the Friday sermon embodies the principles of religious moderation. There are three principles of religious moderation: the principle of justice, commonly referred to as I'tida>l, the principle of balance known as Tawa>zun, and the principle of tolerance called Tasamuh. The concept of justice or I'tida>l is understood as steady and direct. From I'tida>l in various sermons, commendable tales of the Prophet and anecdotes from everyday life can be regarded as just. The congregation's reaction reiterated the same message, often reminding them to act fairly when behaving or selecting a leader. Tawazun The preacher consistently urges the congregation to fulfill their responsibilities as human beings and servants of Allah, which includes duties such as a husband continually supporting his family and worshipping Allah SWT. Tasamuh refers to the community's acceptance of not bothering individuals who are different from them.